Social and Cultural of Stigma For Children With Stunting: A Literatur Review - Hisyam, Badrul Nurul; Susanto, Tantut (Babali Nursing Research, 2025)
Background: Children living with stunting face unique challenges influenced by social and cultural factors. Social stigmas arising from traditional cultures, norms, and beliefs exacerbate families' access to health services and negatively impact children's mental and emotional well-being. This literature review aims to identify factors related to social and cultural stigma affecting children with stunting within communities. Methods: This study employed a literature review design, utilizing a selection and evaluation process guided by the PRISMA protocol and checklist. The inclusion criteria included articles discussing the impact of socio-cultural stigma on stunting, qualitative or quantitative studies published between 2016 and 2024, and articles written in English or Indonesian with full access. The exclusion criteria comprised non-relevant articles focused solely on medical aspects without an association to stigma and literature presented only as general reviews without empirical data. Results: Social, cultural, and economic factors, including poverty, low parental education levels, and gender role disparities, contribute to the prevalence of stunting among children. The stigma associated with stunting negatively affects children's overall health. These children often experience discrimination and social isolation due to their physical condition, further impacting their mental well-being. Conclusion: Social and cultural stigmas are significantly related to stunting among children in Indonesia. Therefore, culturally sensitive and community-based approaches should be integrated into health services to reduce stigma within communities.